PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA BIDANG STUDI SAINS KELAS VI SDN 1 BIROMARU - Cicilia, Vivien (JSTT, 2015)
Lack of learning activities and outcomesin science subject are the main problems faced by year VI of State Primary School 1 of Biromaru. The research was a class room action experiment using Kemmis and Mc. Taggart model with two cycles. The cycles included different stages such as planning, implementation, observation and reflection. The research subject was 24 students with various learning capability consisting of 10 males and 14 females of year VI of Biromaru state primary school 1. The achievement results showed that the students’ learning activities in the cycle 1 and 2 was well implemented and the learning achievement in the science subject had improved as suggested by learning indicator achievement both in individual comprehensionthe classical mastery learning. It is concluded that the implementation of learning model of reciprocal teaching in science subject can improve the learning activities and achievement of year VI students of state primary school 1 of Biromaru.